Exploring the factors and impacts of flash floods vulnerability in various areas of malaysia: A content analysis - Mohammad Syamsyul Hairi, Saad; Mohamad Idris, Ali; Putri Zulaiha, Razi; Noram Irwan, Ramli; Putra Jaya, Ramadhansyah (Popular Scientist, 2024)
The rising flash floods disrupt communities, damage infrastructure, and strain economic resources, highlighting the urgent need for effective flood management strategies. This study examines the causes and impact of flash floods in Malaysia to provide a holistic understanding and actionable insights for flood risk management. A comprehensive content analysis was performed from 2013 to 2023, utilizing scholarly articles, governmental reports, and newspaper data. The research identifies key causes contributing to flash flood vulnerability, including inadequate drainage systems, rapid urbaniza-tion, reclamation projects, developer negligence, and insufficient urban planning as specific activities associated with new development projects. These activities disrupt natural water flows, increasing runoff and flood risks. The analysis indicates that flash floods disrupt daily life and economic activities, such as the construction industry, leading to project delays and in-creased costs. This research contributes significantly to flood risk manage-ment by highlighting the importance of integrating resilient design tech-niques, enhanced coordination among local authorities, enforcing stricter regulations, and promoting sustainable development practices. It provides a foundation for future research and policymaking aimed at reducing flash flood vulnerability. The findings recommend future of flood management lies in breaking down silos between engineering, planning, and environmen-tal management, ensuring that guidelines such as MASMA, NPP, and the USMM work in unison toward a common goal of flood resilience.